The role of environmental taxes and stringent environmental policies in attaining the environmental quality: Evidence from OECD and non-OECD countries - Chen, Mingliu; Jiandong, Wen; Saleem, Hummera (Frontiers in Environmental Science, 2022)
Numerous economies focus on attaining a clean environment by applying environmental policies and green technology. This study examined the impact of GDP growth, non-renewable, technological change, environmental tax, and strict regulations on an ecological footprint for the Organization for Economic Cooperation and Development (OECD) and Non-OECD (not members of OECD) economies from 1990 to 2015. This analysis applied the Cross-Sectionally Augmented Auto-Regressive Distributed Lag (CS-ARDL) to identify the role of GDP, and environmental taxes, with selected control factors on ecological degradation. These CS-ARDL techniques resolve the issues of slope heterogeneity, endogeneity, and cross-sectional dependence. For robustness, this study used Augmented Mean Group (AMG), and Common Correlated Effect Mean Group (CCEMG) tests to check the long-run association between variables. The empirical findings of CS-ARDL have confirmed that environmental taxes, stringent environmental policies, and ecological innovation significantly improve environmental quality in OECD compared to the Non-OECD countries. The D-H panel Granger causality test results show the unidirectional causality moving from environmental tax to ecological footprint, which referred to the "green dividend" hypothesis of minimizing environmental degradation. Using AMG and CCEMG tests for Robustness checks indicates that environmental taxes and tight environmental policy can effectively improve the environment's quality in both regions. Hence, environmental protection awareness is forcing policymakers to minimize the impact of environmental degradation to achieve sustainable growth.